Amphibians in the climate vise: loss and restoration of resilience of montane wetland ecosystems in the western US - Ryan, Maureen E; Palen, Wendy J; Adams, Michael J; Rochefort, Regina M (Frontiers in ecology and the environment, 2014)
Wetlands in the remote mountains of the western US have undergone two massive ecological "experiments" spanning the 20th century. Beginning in the late 1800s and expanding after World War II, fish and wildlife managers intentionally introduced millions of predatory trout (primarily Oncorhynchus spp) into fishless mountain ponds and lakes across the western states. These new top predators, which now occupy 95% of large mountain lakes, have limited the habitat distributions of native frogs, salamanders, and wetland invertebrates to smaller, more ephemeral ponds where trout do not survive. Now a second "experiment" - anthropogenic climate change - threatens to eliminate many of these ephemeral habitats and shorten wetland hydroperiods. Caught between climate-induced habitat loss and predation from introduced fish, native mountain lake fauna of the western US - especially amphibians - are at risk of extirpation. Targeted fish removals, guided by models of how wetlands will change under future climate scenarios, provide innovative strategies for restoring resilience of wetland ecosystems to climate change.